2012
DOI: 10.1038/ijo.2012.196
|View full text |Cite
|
Sign up to set email alerts
|

Catch-up growth following intra-uterine growth-restriction programmes an insulin-resistant phenotype in adipose tissue

Abstract: Background:It is now widely accepted that the early-life nutritional environment is important in determining susceptibility to metabolic diseases. In particular, intra-uterine growth restriction followed by accelerated postnatal growth is associated with an increased risk of obesity, type-2 diabetes and other features of the metabolic syndrome. The mechanisms underlying these observations are not fully understood.Aim:Using a well-established maternal protein-restriction rodent model, our aim was to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 53 publications
9
82
1
1
Order By: Relevance
“…Numerous studies have concluded that IUGR individuals, especially those with postnatal accelerated growth, are prone to develop insulin resistance and T2DM in adulthood (11)(12)(13). Using a well-established rodent model, these experiments have found that CG-IUGR rats had higher methylation level of specific CpG sites of PGC-1α promoter, in contrast, reduced PGC-1α transcription activity, mitochondrial content as well as protein level of key components of insulin-signaling pathway in liver and muscle tissues.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous studies have concluded that IUGR individuals, especially those with postnatal accelerated growth, are prone to develop insulin resistance and T2DM in adulthood (11)(12)(13). Using a well-established rodent model, these experiments have found that CG-IUGR rats had higher methylation level of specific CpG sites of PGC-1α promoter, in contrast, reduced PGC-1α transcription activity, mitochondrial content as well as protein level of key components of insulin-signaling pathway in liver and muscle tissues.…”
Section: Discussionmentioning
confidence: 96%
“…Many intrauterine growth restriction (IUGR) infants experience postnatal accelerated growth (8), begetting shortterm (9) and long-term health benefits, especially in cognition and academic achievement (10). However, emerging evidence suggests that IUGR followed by postnatal accelerated growth (CG-IUGR) plays a role in the programing of adult metabolic disease risk (11)(12)(13), and the underlying molecular pathogenesis is unclear. Nevertheless, the epigenetic dysregulation has been implicated.…”
mentioning
confidence: 99%
“…Venu et al 28 reported that maternal Mg restriction increased pup body adipose percentage, and reduced lean body and fat-free mass at postnatal 90 days. Berends et al 29 found that pups from protein-restricted diet mothers had higher adipocytes at 22 days and 3 months. Maternal zinc deficiency increased body adipose ratio in offspring at six months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Since 'catch-up growth' has been reported to increase the risk of adult NCDs, 21,31,38,[69][70][71][72][73][74][75][76] nutritional interventions for nursing women and/or neonates may be another target for early interventions (Figure 8). However, Houk et al 102) demonstrated that children born small for gestational age without 'catch-up growth' were at high risk of short stature in adulthood and should be referred for growth hormone treatment.…”
Section: Candidates For Early Interventions In Perinatal Medicinementioning
confidence: 99%